Changes in cell wall polysaccharides during water stress in wheat genotypes varying in drought tolerance - Leucci M.R.; Lenucci M.; Piro G.; Dalessandro G. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The in vivo changes of cell wall polysaccharides were studied in apical root segments excised from water-stressed and unstressed wheat seedlings (Triticum durum, Desf.) cv. Capeiti drought tolerant and cv. Creso drought sensitive. In both cv., the total amount of cell wall matrix polysaccharides (pectins and hemicelluloses), sequentially solubilised with CDTA/Na2CO3 and KOH, and of the insoluble residue (a-cellulose) was unaffected by the stress. However, a reduction in the amount of solubilised pectins in favour of an increase of hemicelluloses was evidenced in stressed cv. Capeiti. Stress determined little variations in the glycosyl residue composition of pectins, hemicelluloses and a-cellulose of root apical segments of both cv., nevertheless, the glycosidic linkage analyses indicated that the root apex of the drought tolerant cv. Capeiti subjected to water stress, synthesises cell wall polysaccharides with a higher capability of binding water which could play an important role in water stress tolerance.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)